THE PLACE OF MOBILE APPLICATIONS IN THE PRODUCTION OF SECONDARY HOMASHO (Archive of Conferences, 2020)
Strategy, goals and objectives for the implementation of waste management in the Republic of Uzbekistan for 2019-2028, effective ways to achieve them, priority areas, as well as the long-term perspective system of sustainable development. The formation of this system envisages the gradual development of the old methods used in the implementation of work on household waste with the transition to modern advanced methods available in today's world.